Beliefs on COVID-19 Among Electronic Cigarette Users: Behavioral Responses and Implications for COVID Prevention and E-Cigarette Interventions. (April 2021) - Kelly, Brian C.; Pawson, Mark; Vuolo, Mike
E-cigarette users' beliefs about COVID-19 may shape their responses to the pandemic and their e-cigarette consumption. A U.S. national cross-sectional survey of 562 e-cigarette users was conducted in April 2020. Participants self-reported nicotine consumption, COVID-19 beliefs, beliefs about e-cigarettes, social distancing, COVID-19 disruptions, cessation considerations, and individual characteristics. Ordinary least squares (OLS) regression provided unstandardized, and standardized coefficients. Frequency of e-cigarette use is inversely associated with beliefs COVID-19 is relevant (β = −0.215). Beliefs e-cigarettes are addictive, harmful, or pose a risk to future health were positively associated with beliefs COVID-19 is relevant (β = 0.171; β = 0.164; β = 0.203), beliefs the media are truthful on COVID-19 (β = 0.133; β = 0.136; β = 0.137), and beliefs e-cigarette users are at greater risk (β = 0.279; β = 0.411; β = 0.447). All three COVID-19 beliefs (COVID relevant; media truthful; and greater risk) were positively associated with social distancing (β = 0.307; β = 0.259; β = 0.115), work disruptions (β = 0.134; β = 0.135; β = 0.130), family disruptions (β = 0.232; β = 0.131; β = 0.164), friendship disruptions (β = 0.214; β = 0.139; β = 0.133), and considerations of quitting (β = 0.250; β = 0.222; β = 0.620). Strong associations between e-cigarette beliefs and COVID-19 beliefs exist. COVID-19 beliefs are associated with behavioral responses, such as social distancing and considerations of e-cigarette cessation. Interventions may be able to leverage COVID-19 beliefs to reduce e-cigarette consumption or promote cessation during the pandemic.